2019
DOI: 10.1002/lsm.23069
|View full text |Cite
|
Sign up to set email alerts
|

Vascular‐targeted low dose photodynamic therapy stabilizes tumor vessels by modulating pericyte contractility

Abstract: Vascular‐targeted low‐dose photodynamic therapy (L‐PDT) was shown to improve chemotherapy distribution in malignant pleural tumors such as malignant pleural mesothelioma (MPM). However, the mechanisms triggered by L‐PDT on the tumor vasculature are still debated. In pericyte and endothelial cell co‐cultures, we show that pericytes exhibit enhanced sensitivity towards L‐PDT compared to endothelial cells, displaying actin stress fibers and cellular contraction via Rho/ROCK kinase signaling myosin light chain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…Additionally, a significant increase in the phosphorylation of MLC (a Rho-kinase downstream effector) was detected at 5, 15, and 30 min post TS-PDT administration ( Figure 4 ). Several studies have demonstrated the importance of the RhoA/ROCK pathway in pericyte contractility and activation [ 24 , 40 ]. Y27632, a synthetic pyridine derivative that inhibits ROCK by competing with ATP for the active site of the kinase, was able to impair the TS-PDT-induced phosphorylation of MLC ( Figure 5 a,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a significant increase in the phosphorylation of MLC (a Rho-kinase downstream effector) was detected at 5, 15, and 30 min post TS-PDT administration ( Figure 4 ). Several studies have demonstrated the importance of the RhoA/ROCK pathway in pericyte contractility and activation [ 24 , 40 ]. Y27632, a synthetic pyridine derivative that inhibits ROCK by competing with ATP for the active site of the kinase, was able to impair the TS-PDT-induced phosphorylation of MLC ( Figure 5 a,b).…”
Section: Discussionmentioning
confidence: 99%
“…The vascular shutdown effect is commonly known to be photosensitizer dependent [ 19 ]. The selective vascular effects of TS have been demonstrated in preclinical studies [ 20 , 21 , 22 , 23 , 24 ]. Compared with porfimer-based PDT, TS-PDT resulted in a more significant vascular shutdown effect and consequently greater tumor necrosis resulting from ischemia [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other non-invasive imaging systems that have been used or currently under development for evaluation of dermal vasculatures include laser Doppler flowmeter, laser Doppler imaging, dermoscopy, cross-polarized diffuse reflection color imaging system, and optical coherence tomography [39][40][41][42][43][44][45][46][47][48]. The main feature of RCM is that it can directly reveal the dermal structure in a simple and fast way, which makes it be a promising bedside tool for prognostic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when liposomal doxorubicin was administered following L‐PDT treatment, the drug penetrated significantly deeper into the tumor tissue compared to the control. Recently, Cavin et al explored the mechanism through which L‐PDT alters vasculature to modulate IFP. Using a pericyte and endothelial cell coculture, they found that PDT alters the function of pericytes, strengthening their association with endothelial cells.…”
Section: Targeting the Tumor Microenvironment With Photochemistrymentioning
confidence: 99%